The apoptotic and anti-metastatic effects of niosome kaempferol in MCF-7 breast cancer cells - Shinoo Minaei; Mahsa Kavousi; Faranak Jamshidian (Scientific Reports)
Abstract Kaempferol (KMF) possesses notable anti-tumor bioactivity, which indicates its promising action in the therapy of gynecologic cancers. Here, we examined the therapeutic potential of the naturally occurring flavonoid kaempferol coated on niosome nanoparticles (NPs) and its impact on the breast cancer cell line MCF-7. Niosome NPs containing KMF were prepared by thin-layer hydration. The generated niosome/KMF NPs cytotoxicity on MCF-7 and MCF-10 cell lines were assessed by MTT assay. The physicochemical properties of the niosome/KMF NPs were characterized by SEM, DLS zeta potential, and FTIR. Flow cytometry was used to quantify primary and secondary apoptosis, necrosis and cell cycle arrest. Finally, the expression of apoptosis (Bax and caspase 3) and metastasis genes (ITGA5 and MMP2) was analyzed by Real-time PCR. A Scratch test was performed to investigate the anti-metastatic effect of synthesized nanoparticles. The results showed that the synthesized niosome/KMF NPs have a diameter of 500 nm, a zeta potential of 33.9 mV and a PDI of 0.169. The FTIR spectrum of niosome NPs containing KMF showed distinct peaks in the range of 600–3400 cm− 1 belonging to different components. The results of the MTT assay showed that treatment of the MCF-7 cell line with a concentration of 0.0873 µMol of niosome NPs containing KMF resulted in the death of 50% of the cells. Niosome/KMF NPs caused 64% apoptosis in MCF-7 cells. Real-time PCR results showed a 2.95- and 2.75-fold increase in Bax and caspase 3 gene expression compared to the control group (p < 0.001). After 72 h of treatment with niosome NPs containing KMF, ITGA5 and MMP2 gene expression decreased by 0.58- and 0.53-fold, respectively (p < 0.001). In summary, KMF-loaded niosome NPs efficiently induced apoptosis and inhibited metastasis-related gene expression in MCF-7 cells, exhibiting notable anti-cancer activity.